A simulator study of the effect of incentive on adoption and effectiveness of an in-vehicle human machine interface. (January 2019) - Vaezipour, Atiyeh; Rakotonirainy, Andry; Haworth, Narelle; Delhomme, Patricia
Highlights: Effectiveness of eco-safe in-vehicle human machine interface with incentive evaluated. Drivers who perceived themselves to be safer drivers prefer advice only systems. The in-vehicle HMI with incentive further reduced fuel consumption by 4.7%. Abstract: Introduction: Rapid developments in transportation technologies, such as in-vehicle human-machine interfaces (HMI), have the potential to improve driving behaviour. However, the use of such approaches is typically voluntary and there are numerous barriers to their widespread implementation. The aim of the current paper is to evaluate the impact of monetary incentive combined with competition with other drivers on adoption and effectiveness of an eco-safe in-vehicle HMI. Moreover, this research assess intentions to use and willingness to purchase the in-vehicle HMI, both of which play crucial roles in sustained voluntary uptake of in-vehicle HMIs. Method: Forty drivers participated in a driving simulator experiment and questionnaires. Three variations of an eco-safe driving in-vehicle HMI were evaluated (advice only, feedback only, combined advice and feedback), followed by an incentive-based condition. Results: The findings revealed the 4.7% reduction in fuel consumption with an addition of incentive and competition with other drivers associated with the use of in-vehicle HMI on eco-safe driving behaviour. Moreover, there was some evidence to suggest that a range of extrinsic and intrinsic incentives may be beneficial for increasing intentions to use such a system. Conclusions: We conclude that the addition of incentives may be more effective in encouraging greater intentions to use the in-vehicle HMI, compared to improving eco-safe driving behaviour associated with system use. Practical applications: This research provides valuable knowledge towards enhancing the current understanding of the nature and features of eco-safe in vehicle HMIs. Such information provides a foundation for the design and development of novel in-vehicle systems, incorporating the influence of competition with other drivers and incentives to enhance the motivation to use in-vehicle systems and consequently, improve drivers' fuel efficiency and safe driving behaviour.